충청남도 지역 2018년 초여름 대기환경기준물질 농도의 시간적 · 공간적 변화 분석 - 이복진(Bok-Jin Lee); 박승식(Seung-Shik Park) (한국대기환경학회지(국문), 2019)
Stationary sources such as coal-fired power plants, steel works, and petrochemical plants emit significant amounts of air pollutants to the atmosphere. Generally, SO2 and NOx from the large-scale stationary sources convert to the SO4 2- and NO3 - particles through atmospheric chemical transformation processes, respectively, resulting in increase in ambient PM2.5 concentration. It has been reported that large-scale coal-fired power plants and steel works in the west coast areas of Chungcheongnam-do could be important sources of PM2.5 in the metropolitan area and other downwind regions. In the near future, the National Strategic Project-Fine Particle makes a project to conduct aircraft measurements in the west coast region to investigate transport pathways of air pollutants coming from polluted Chinese regions and to impact of air pollutants from the large-scale stationary sources in the region. In this study, as a part of this project, concentrations of criteria air pollutants (PM10, PM2.5, CO, O3, NO2, and SO2) observed at 10 air quality monitoring networks during May~June, 2018 in Chungcheongnam-do were examined to understand the difference in the concentrations of the air pollutants among the monitoring sites and to find out the impact of large-scale stationary sources (coal-fired power-plants, steel works, and petrochemical facilities) on the air quality at downwind sites. Results from the study indicated that monthly average and hourly maximum concentrations of PM10, PM2.5, CO, O3, and SO2 were found to be the highest at the monitoring site around a large-scale steel works. In addition, the PM10 and SO2 concentrations around the steel works showed similar diurnal patterns and rapid increases between 12:00 and 20:00. However, the PM10, PM2.5, and SO2 were low at monitoring sites around two coal-fired power plants. When considering emission inventory of PM, SO2, and NOx from the coal-fired power plants in Chungcheong-namdo province, relatively low concentration levels of PM10, PM2.5, and SO2 around the two coal-fired power plants were likely attributed to meteorological conditions and short distance between the power plants and air quality monitoring sites. KCI Citation Count: 0